Place of cognitive remedition therapy in the management of autism spectrum disorder - Hajri, Melek (International Journal of Psychosocial Rehabilitation, 2017)
Background : Autism Spectrum Disorder (ASD) is known to be associated with Cognitive impairment, especially executive dysfunction. Cognitive Remediation Therapy (CRT) is a novel rehabilitation method aiming to produce improvement in cognitive processes. CRT has been used in patients with schizophrenia. Taking into account the overlap between ASD and schizophrenia, the aim of our study was to adapt and apply the cognitive remediation program CRT for children and adolescents with autism spectrum disorder, and evaluate its effectiveness on the executive functions, clinical symptoms and school performance. Methods: A cross-sectional study conducted with children and adolescents with autism spectrum disorder according to the DSM-5 criteria. The program called CRT was provided at the rate of one session (duration = 45 minutes) per week. The patients were evaluated before the beginning of the intervention and one week after its end. The evaluated parameters were intellectual abilities, cognitive flexibility, inhibition, working memory, planning, clinical symptoms and school results.